2021
DOI: 10.1177/19322968211012392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carbohydrate Counting Error on Glycemic Control in Open-Loop Management of Type 1 Diabetes: Quantitative Assessment Through an In Silico Trial

Abstract: Background: In the management of type 1 diabetes (T1D), systematic and random errors in carb-counting can have an adverse effect on glycemic control. In this study, we performed an in silico trial aiming at quantifying the impact of different levels of carb-counting error on glycemic control. Methods: The T1D patient decision simulator was used to simulate 7-day glycemic profiles of 100 adults using open-loop therapy. The simulation was repeated for different values of systematic and random carb-counting error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This baseline system is represented as HAID SBC MCHO. The CHO misestimation error is incorporated as a Gaussian distribution according to the recently published methodology 41 . To implement the SBC, the parameters required are the carbohydrate-to-insulin ratio (CR) and correction factor (CF), calculated based on clinical guidelines 42 .…”
Section: Resultsmentioning
confidence: 99%
“…This baseline system is represented as HAID SBC MCHO. The CHO misestimation error is incorporated as a Gaussian distribution according to the recently published methodology 41 . To implement the SBC, the parameters required are the carbohydrate-to-insulin ratio (CR) and correction factor (CF), calculated based on clinical guidelines 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Accuracy and consistency in carbohydrate counting are important to optimize postprandial glycemia and reduce glucose variability 126,127 . There is no universal definition for accuracy of carbohydrate counting.…”
Section: Education Tools Methods and Insulin Regimensmentioning
confidence: 99%
“…125 Accuracy and consistency in carbohydrate counting are important to optimize postprandial glycemia and reduce glucose variability. 126,127 There is no universal definition for accuracy of carbohydrate counting. Research has shown that children, adolescents and their parents can carbohydrate count with a degree of accuracy, however under and over-estimation of foods remains a challenge.…”
Section: Carbohydrate Assessment and Methodsmentioning
confidence: 99%
“…Combined with the fact that CYP are already managing the diagnosis of a life-long health condition and having to develop complex self-management and behavioural skills, it is not surprising that T1DE can develop. The focus on carbohydrate counting, whilst beneficial to attain euglycaemia ( 10 ) can lead to several psychological difficulties with food, impacting both individual and family dynamics. Foods containing carbohydrate can start to be perceived as ‘bad’ and thus avoided or prohibited within families.…”
Section: Introductionmentioning
confidence: 99%